Quantifying the interactive effects of temperature, CO2, and irrigation levels on peanut yield and quality - Rajanna G Adireddy; Saseendran S Anapalli; Krishna N Reddy; Prasanna H Gowda (Plant Stress)
The interplay between increases in air carbon dioxide concentration (eCO2) and temperature (Ta) and changing irrigation water availability presents challenges and opportunities for crop production. Increasing eCO₂ can improve photosynthesis and growth; however, such benefits can be nullified by the adverse effects of higher temperatures on plant physiological processes, particularly under water-limited conditions. In this context, this study quantified phenology, shoot and root growth, and seed yield and quality of peanut (Arachis hypogaea L.) grown under weather extremes with (1) air eCO2 level of 420 ppm and measured hourly air temperature (Ta) in a nearby crop field in 2024 (CC420), (2) eCO2 at 570 ppm and Ta increased by 3 ⁰C (PC570), and (3) eCO2 at 780 ppm and Ta increased by 5 ⁰C (PC780). Two peanut cultivars (NuMex-01 and Olin) were evaluated with two irrigation levels using a split-plot design with four replications. Under PC780, both cultivars exhibited significantly higher root and shoot growth and number of flowers and pegs than CC420, as reflected in the above-ground biomass increase of 49–94 %. However, plants matured ∼10 days earlier and significantly reduced kernel yield, pod yield, harvest index, and oil yields by 67.2 %, 61.6 %, 73.4 %, and 87.4 %, respectively. In the PC570 and PC780, photosynthetic rates were enhanced during the early crop stage but decreased during the pod development stage than CC420. Further, peanut seed quality deteriorated under PC570 and PC780 by enhancing seed palmitic and palmitoleic acid contents. Irrigations applied at FC100 exhibited significantly better kernel (24.6 g), pod (36.9 g), biomass (108.9 g), and oil (16.8 g) yields compared to FC50. Among cultivars, NuMex-01 exhibited 35 %, 42 %, 51 %, and 20 % significantly higher kernel yield, pod yield, harvest index, and oil yield than the Olin cultivar. To summarize, when a significant enhancement in biomass growth due to the eCO2 fertilization effect was measured, the adverse effects of associated temperature rise resulted in a significant decrease in peanut yield and quality. Developing cultivars with enhanced resilience to temperature extremes may be required to sustain peanut production under increasing weather extremes.